Regulation of Human Antithrombin Gene Expression. (1) Mapping of a Deletion Including in Part the Promoter Region. (2) Characterization of Cis-Acting Elements and Transcription Factors Binding to This Region - Fernandez-Rachubinski, Francoise (My University, 1996)
This thesis addresses regulatory aspects of the constitutive expression of human antithrombin, a serine-protease inhibitor involved in coagulation and thrombosis. An introductory part describes a 5'partial deletion, 480 nt upstream of the third exon of an antithrombin allele, in a kindred with thrombosis and hereditary deficiency in antithrombin. The lack of expression of the abnormal allele prompted the further characterization of elements regulating transcription in the 5' region of the normal antithrombin gene. Two cis-acting elements were found, both able to promote transcription in HepG2 and Cos I cells. The first promoter, at -150/+68 nt, encompassed the presumed transcriptional start site. The second element, in reverse orientation in regard to the first, was located at +895/+391 nt in the first intervening sequence. Following footprint analysis, it was shown that the 5'upstream promoter interacted with trans-acting factors at -92/-65 nt, -11/+37 nt and -124/-10 nt, in nuclear extracts from hepatic or non-hepatic origin. Several transcription-factors were subsequently identified, which interacted with these three elements either through direct binding or heterodimerization; they were the liver-enriched factors HNF4 and C/EBPα as well as the ubiquitous nuclear hormone receptors COUP-TF1, RXRα, PPARα and TRα. Furthermore, in vivo expression in HepG2, HeLa and BSC40 cells, of HNF4, C/EBPα and RXRα increased the efficiency of the 5'upstream promoter, while expression of COUP-TFl, TRα, HNF3α or β repressed the efficiency of the latter promoter and the activating effects of HNF4. In addition, activation by HNF4 was synergized by co-expression of RXRα in BSC40 and HeLa cells. These results suggest that the interplay of liver-enriched and ubiquitous factors modulates the constitutive expression of the antithrombin gene.
Keywords: Medical Sciences; Medical Sciences